An eye for talent: The recruiters` role in the Australian Football talent pathway - Larkin, P.; Marchant, D.; Syder, A.; Farrow, D. (PLOS ONE, 2020)
Talent identification and recruitment (TIR) in elite sport is a complex process with performance and career longevity implications for athletes, sports organisations, and scouts (hereafter referred to as recruiters). Although there is an established body of published research on TIR the critical roles that recruiters perform has only recently gained attention from researchers. In this study, we report on the practices that 12 full time Australian Football recruiters use to inform their TIR decisions. Inductive qualitative semi-structured interviews were conducted using open-ended questions. Thematic analysis resulted in the identification of four primary themes (the recruiter, processes and practices, assessment and selection). The results and discussion provide insights and an occupational `road map` into the important role recruiters perform in sporting organisations.